A Corpus-Based Pilot Study of the Pop Lyrics on Billboard - Chen Yang (Unisia, 2021)
Although pop music is endorsed as one of the most leisure activities to express feelings and emotions in people’s daily life, song lyrics are usually neglected by linguists and excluded in any of English corpora (e.g., BNC and ANC) that are currently adopted. The current study focuses on an analysis of lyrics based on a Billboard music chart corpus mainly containing American pop lyrics, via both qualitative and quantitative methods, and aims to investigate to what extent the lexico-grammatical features of the words and expressions used in lyrics enable those songs widely accepted by audience. Results reveal that conversational contexts in the lyrics mark a story-telling feature, and help audience easily realize artists’ attitudes and the implications to some events and scenarios.